Molecular symmetry - Willock, David J. (John Wiley & Sons, 2009)
An accessible introduction to symmetry and spectroscopy, this text examines symmetry in nature and chemistry, point groups, the interaction of light with molecules, electronic spectra of transition metal complexes with a final chapter on symmetry and the spectra of complexes.